Effect of some chemicals on incidence of poato soft rot disease in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2017)
Bactericidal effect was investigated by chemicals against potato soft rot bacteria in vitro and in storage. The chemicals were acetic acid, boric acid, bleaching powder, lactic acid, calcium hydroxide, calcium chloride, potassium chloride and sodium hypo-chloride. Among eight  chemicals only three chemicals viz. acetic acid, boric acid and bleaching powder showed bactericidal activity against potato soft rot bacteria  Pectobacterium carotovorum subsp. carotovorum (E. carotovora subsp. carotovora) P-138 in vitro. Based on the results of in vitro experiment three chemicals, acetic acid, boric acid and bleaching powder were used to control soft rot disease of potato in storage. Fresh potato tubers were dipped in 0.2% solution/suspensions of acetic acid, boric acid and bleaching powder for 30 min. Then soft rot bacteria Pectobacterium carotovorum subsp. carotovorum P-138 was inoculated on potato. Finally potatoes were stored for 22 weeks in net bags in sterilized condition. All the three chemicals significantly decreased the infection rate, loss in weight and increased percentage of disease reduction (PDR) of potato. Boric acid was the most effective in controlling the soft rot disease of potato in storage followed by acetic acid and bleaching powder. So these chemicals may be used for seed purpose storage of potato tubers for year round storage at farmers level.Bangladesh J. Sci. Ind. Res. 52(2), 135-140, 2017